Hibrid Δ-Statistical Convergence for Neutrosophic Normed Space - Nazmiye Gonul Bilgin (Journal of Mathematics)
This study is about neutrosophic structures, which is one of the popular topics of recent days. In this study, different types of convergence concepts were applied to difference sequences. With the help of the properties of double type sequences, the concept of difference sequences is combined with structures that are advantageous to work like Lacunary sequences.